ANALISIS TEKNIK PERMAINAN TRADISIONAL EGRANG : KAJIAN GERAK MELANGKAH - Wanda Kusuma Putri; Fajar Awang Irawan (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2025)
The success factor in maintaining balance in the egrang stepping motion is influenced by the consistency of the step length both right and left. Inconsistency in stepping causes balance to be difficult to control. This study aims to analyze the technique of traditional egrang game in stepping motion. This research method is descriptive analysis. The sample in this study amounted to 16 people who are members of KDOT (Komunitas Dolanan dan Olahraga Tradisional) Universitas Negeri Semarang. The analysis focused on step distance with the help of Kinovea Software version 0.9.5 and the data was described descriptively for analysis and recommendations. Indicators of success in the consistency of egrang step length found that the average distance of 1 step 101.97 ± 18.00 cm; right step length 53.29 ± 9.57 cm; and left step length 48.44 ± 10.36 cm. This study found that the stride length strategy in the traditional egrang game is smaller than the normal human stride without egrang. This research is limited only to the step length factor, it is hoped that further research will pay attention to the length of time in maintaining balance when playing egrang.